1994
DOI: 10.1128/mcb.14.7.4335
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 associates with the beta c chain of the receptor for granulocyte-macrophage colony-stimulating factor, and its activation requires the membrane-proximal region.

Abstract: The high-affinity receptor for granulocyte-macrophage colony-stimulating factor (GM-CSF) consists of a unique a chain and a Pc subunit that is shared with the receptors for interleukin-3 (IL3) and . Two regions of the Pc chain have been defined; these include a membrane-proximal region of the cytoplasmic domain that is required for mitogenesis and a membrane-distal region that is required for activation of Ras, Raf-1, mitogen-activated protein kinase, and S6 kinase. Recent studies have implicated the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
319
2
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(328 citation statements)
references
References 35 publications
6
319
2
1
Order By: Relevance
“…The membrane proximal intracellular portion of the receptor till amino-acid number 589, that includes the Box 1 region, was shown to be necessary and su cient for DNA synthesis mediated by several of these cytokines including IL-3 (Sato et al, 1993;Tian et al, 1996). This region was also found to be required for the induction of proliferation-associated genes such as c-myc, pim-1 and oncostatin M. Following cytokineinduced hetero-dimerization, this region of the receptor was found to bind to multiple signal-transducing proteins, which include JAKs, STATs, c-Src, phosphotidylinositol-3 kinase as well as Vav (Quelle et al, 1994;Jaster et al, 1997;Yoshimura et al, 1995Yoshimura et al, , 1998Rao and Mufson, 1995;Matsuguchi et al, 1995). The membrane distal domain of the receptor, spanning amino acids 589 Ā± 881, was shown to be required for growth inhibition that can be induced by some of the cytokines.…”
Section: Interleukin-3 (Il-3) and Its Receptor (Il3-r)mentioning
confidence: 99%
“…The membrane proximal intracellular portion of the receptor till amino-acid number 589, that includes the Box 1 region, was shown to be necessary and su cient for DNA synthesis mediated by several of these cytokines including IL-3 (Sato et al, 1993;Tian et al, 1996). This region was also found to be required for the induction of proliferation-associated genes such as c-myc, pim-1 and oncostatin M. Following cytokineinduced hetero-dimerization, this region of the receptor was found to bind to multiple signal-transducing proteins, which include JAKs, STATs, c-Src, phosphotidylinositol-3 kinase as well as Vav (Quelle et al, 1994;Jaster et al, 1997;Yoshimura et al, 1995Yoshimura et al, , 1998Rao and Mufson, 1995;Matsuguchi et al, 1995). The membrane distal domain of the receptor, spanning amino acids 589 Ā± 881, was shown to be required for growth inhibition that can be induced by some of the cytokines.…”
Section: Interleukin-3 (Il-3) and Its Receptor (Il3-r)mentioning
confidence: 99%
“…Phosphorylated tyrosine residues on bc then serve as docking sites for intracellular signalling molecules, for example, STAT transcription factors and adapter molecules such as Shc (Chin et al, 1996;Lanfrancone et al, 1995). Non-phosphotyrosine mediated interactions have been reported for Jak2 (Quelle et al, 1994) and members of the Src family of kinases (Al-Shami et al, 1997). We have performed a two-hybrid screen with a HeLa cell library, utilizing the cytoplasmic domain of human bc lacking the box1 region (bc cyt Dbox1) to assess the occurrence of other tyrosine phosphorylation independent interactions.…”
mentioning
confidence: 99%
“…Although bc contains no intrinsic kinase domain, upon ligand binding, rapid tyrosine phosphorylation of many cellular proteins, including the receptor itself is observed. (Quelle et al, 1994;Eder et al, 1993) Recent studies have demonstrated that the tyrosine kinase Jak2 is associated with the bc in a region containing a peptide stretch known as the box1 homology domain (Quelle et al, 1994) which is conserved among many cytokine receptors (Murakami et al, 1991). Its association with bc has been shown to be critical for receptor phosphorylation and downstream signalling.…”
mentioning
confidence: 99%
“…There was a report showing an essential and su cient role of JAK2 activation through the plasma membrane proximal domain of erythropoietin receptor (EPOR) for anti g irradiation-induced apoptosis in 32D cells (Quelle et al, 1998). The observation that the box1 region of EPOR and bc exerts activity through interaction with JAK2 (Quelle et al, 1994;Witthuhn et al, 1993), also means that only JAK2 is essential and su cient for prevention of the apoptosis induced by g irradiation. Our attempt to conĀ®rm this point using chimeric bc/JAK2 constructs (Liu et al, 1999a) revealed that BA/F3 cells expressing b-JAK2 failed to suppress the DNA fragmentation induced by g irradiation.…”
Section: Role Of Jak2 In Anti G Irradiation-induced Apoptosismentioning
confidence: 99%
“…JAK2 plays an essential role for various hGM-CSF activities and that JAK2 activation depends on the box1 region of bc (Quelle et al, 1994;Watanabe et al, 1996). Since deletion of the box1 region abrogated the potential for hGM-CSFR to maintain cell survival, JAK2 is likely to play an essential role in transducing signals for anti g irradiation-induced apoptosis.…”
mentioning
confidence: 99%